Kewenangan Pemerintah Dalam Pengadaan Tanah Untuk Kepentingan Umum - Muwahid Muwahid (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
The government, in carrying out land acquisition for the public interest, gets the authority of attribution in Law No. 5 of 1960 about the Basic Agrarian Principles (UUPA) as contained in article 2, article 6, and article 18. On the oher hands, the government also gets the attributional authority of Law No. 20 of 1961 about revocation of land rights, and Law No. 2 of 2012 about land acquisition for development of the public interest. However, in the laws and regulations governing land acquisition in the public interest, there is an inconsistency in regulation between Law No. 2 of 2012 and Law No. 20 of 1961. Several articles in Law No. 2 of 2012 deny the provisions regulated in Law No. 20 of 1961. Even though Law No. 20 of 1961 is still valid because it has never been revoked or replaced with other laws and regulations. Beside that, there is an overlapping arrangement between Law No. 2 of 2012 and Law No. 20 of 1961. Keywords: Authority, Government, Land Procur